2019
DOI: 10.4018/jgim.2019040109
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Model of Information Technology Management for Smart Cities

Abstract: This article presents a proposal of conceptual model for public administrations that allows analyzing the level of IT management capacity as an enabler of smart cities from a multidimensional and dynamic approach taking into account technological, institutional and innovation aspects. The model includes five domains (e-government strategy, Public Innovation, Data Management, IT Services and Infrastructure) that are described in terms of key domain areas, objectives and questions. The model was conceptually val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…Today, cities are more polluted than villages. Therefore, cities and other communities must be made more sustainable (Maestre-Gongora and Bernal, 2019). Political leaders who are handling different portfolios and who are closely related to industry can act as influencers and guide industry towards the SDGs (Weerakkody et al , 2011).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Today, cities are more polluted than villages. Therefore, cities and other communities must be made more sustainable (Maestre-Gongora and Bernal, 2019). Political leaders who are handling different portfolios and who are closely related to industry can act as influencers and guide industry towards the SDGs (Weerakkody et al , 2011).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Corresponding users can execute server-side applications only through browsers, and do not need to install special client-side software on their computers. These features of the B/S structure make it easier to upgrade the system, which provides a lot of convenience for the expansion and upgrade of the subsidy management system, thereby reducing the work pressure of the system administrator [11,12]. This is also the main reason why the system adopts B/S structure.…”
Section: System Structure Designmentioning
confidence: 99%
“…• The second strand of literature reports on a mixture of urban planning, political and environmental issues of smart cities. Studies found in this strand generally aimed to define the concept, scope, services and trends of smart city from a macro level (Maestre-Gongora & Bernal, 2019;Kirimtat et al, 2020), establish appropriate policies and plans for smart city development (Caragliu and Del Bo, 2019;Angelidou, 2017), measure the performance of smart cities with diverse indicators (Pinna et al, 2017;, and explore sustainability and environmental effects of smart cities (Aina, 2017;Haarstad and Wathne 2019). • The third strand of literature joins up the first two strands with socio-technical angles that stress on the importance and intersection of information, technology, organization and citizens in smart cities.…”
Section: Smart Citymentioning
confidence: 99%